Life cycle and external fund: perspective of trade-off theory and pecking order theory - Zaki Fakhroni; Irwansyah Irwansyah; Nadhifa Chairunnisa Pattipawaej (Faculty of Economics and Business Mulawarman University, 2022)
The research is to examine the effect life cycle firm’s on external financing (debt) and also this research is conducted to see whether in Indonesia embrace trade-off theory and pecking order theory. This research uses secondary data taken from the financial statment and annual report of manufacturing companies period 2012-2020. Based on the purposive sampling method there were 64 data for 8 years so that it had 512 samples, but have data outlier, so that 464 samples used to get results that are free from multicollinearity problems. This study uses linear regression analysis with categorical data. The results, it shows that: 1) the introduction stage has no significant effect on debt, 2) the growth stage has a significant effect on debt, 3) the mature stage has a significant effect on debt, 4) the stagnant stage has no significant effect on debt 5) the decline stage has a significant effect on debt.